Analisis Kualitas Layanan Aplikasi Livin by Mandiri Terhadap Kepuasan Nasabah Bank Mandiri Yogyakarta - Sherlyanti, Devita Omaya; Albari, Albari (Universitas Negeri Padang, 2024)
In the banking industry to realize service quality and customer satisfaction, Bank Mandiri Area Yogyakarta and the Transaction & Funding Area Unit work together to create a mobile banking product that can be useful and facilitate all types of customer transactions without having to come to a branch office. In this modern era, Bank Mandiri has issued mobile banking that is already known as Livin by Mandiri which has come with a service system, as well as with easy and modern features to support customers' daily banking transactions. This study was made to explain the influence of service quality on a Livin by Mandiri application on Bank Mandiri customer satisfaction in the Yogyakarta Area and to find the truth that the existence of Livin by Mandiri can meet customer satisfaction to transact easily and anywhere. The method used in this study is qualitative description and data collection using observation and interview techniques conducted at the time of the study. The results of the study show that the quality of service at Livin by Mandiri has met customer satisfactionKeywords: Service Quality, Customer Satisfaction, Features.